Experience of migrant care and needs for cultural competence training among public health workers in Korea. Issue 3 (9th February 2018) - Chae, Duckhee; Lee, Jina; Asami, Keiko; Kim, Hyunlye
Abstract: Objective: This study explored the experiences of public health workers (PHWs) providing health care for migrants living in Korea and clarified needs for cultural competence training. Design and Sample: Twenty‐six PHWs from five public health centers in Gwangju city, South Korea, participated in this exploratory qualitative study. Methods: Five semi‐structured focus group interviews of PHWs were conducted from September to December 2016. A directed content analysis approach was conducted using four categories: perceived characteristics of migrants, interaction between PHWs and migrants, interaction between PHWs and organizations/systems, and cultural competence training needs. Results: PHWs perceived that migrants lacked autonomy in health decisions and awareness of health behaviors. PHWs experienced difficulties in communicating and in establishing trusting relationships. They found clients hard to reach and easy to miss, a lack of continuity in health care programs, and inadequate human and material resources. They preferred passive teaching methods to activity‐based simulation. PHWs believed essential training should be provided through e‐learning to all PHWs, including management. Conclusion: PHWs reported experiencing multiple challenges from a lack of preparedness for culturally competent care and their clients' vulnerability. Development of cultural competence training is suggested through e‐learning that reflects the PHWs' experiences and provides systematic support.